Projeto, construção e caracterização do desempenho de um motor de combustão interna provido de um sistema de ignição por lança chamas de carga estratificada - Fernando Antonio Rodrigues Filho (2014)
Vehicular emissions significantly increase the atmospheric air pollution and the green house gases (GHG). This fact associated with the fast global vehicle fleet growth calls for prompt scientific community technological solutions in order to promote a significant vehicle fuel consumption and emission reduction, especially of fossil fuels to comply with future legislation. To meet this goal, a prototype stratified torch ignition engine was created from a commercial existing engine. In this system, the combustion starts in a prechamber, where the pressure increase pushes the combustion jet flames through the calibrated nozzles to be precisely targeted into the main chamber. Those combustion jet flames are endowed with high thermal and kinetic energy being able to promote a stable lean combustion process. The high kinetic and thermal energy of the combustion jet flame results from the load stratification. This is carried out through the direct fuel injection in the pre-chamber by means of a prototype gasoline direct injector (GDI) developed for very low fuel flow rate. During the compression stroke, lean mixture coming from the main chamber is forced into the pre-chamber and, few degrees before the spark timing, fuel is injected in the pre-chamber aiming at forming a slightly rich mixture cloud around the spark plug which is suitable for the ignition and kernel development. The performance of the torch ignition engine running with E25, for different mixture stratification levels, engine speed and load are presented. An analyses of specific fuel consumption, thermal and combustion efficiency, specific emissions of CO, CO2, NOx and THC and the main combustion parameters are carefully carried out. The results obtained in this work show significant increase on the torch ignition engine performance in comparison with the baseline engine used as workhorse for the prototype engine construction. It was obtained a percentage average increase of 6.55% for the specific fuel consumption and of 7.10% for thermal efficiency. For specific emissions was observed a percentage reduction of 8.21% for CO2, 71.58% for CO and 49.51% for NOx.